Cross-border investigation of a tuberculosis outbreak in Vienna linked to a multi-country cluster among foreign-born individuals, Europe, 2021 to 2025 - Adriana Cabal (Eurosurveillance)
Collaborative genomic and epidemiological investigations identified a tuberculosis outbreak in Vienna as part of a multi-country cluster comprising 57 foreign-born cases of Mycobacterium tuberculosis ST215/Beijing 2.2.1 notified 2021–2025. While 14 of 16 cases in Vienna were considered autochthonous, the diverse geographic origin of clustered cases across nine European countries suggests a common transmission source, possibly linked to migratory routes. Cross-border data exchange and integrated genomic analysis are essential for identifying transmission dynamics in tuberculosis clusters affecting mobile populations.